Problemy związane ze zdrowiem psychicznym zgłaszane w Diecezjalnej Poradni Życia Rodzinnego - Krzysteczko, Henryk (Śląskie Studia Historyczno-Teologiczne, 2023)
About 4000 cases were reported and dealt with in the Diocese Family and Pastoral Counseling Center in Katowice in 1986-1999 (Father H. Krzysteczko was the head of the Center at that time) and every case concerned the problems of mental health. The writer of the paper focused his attention mainly on the problems connected with psychic disturbances such as: psychosis, neurosis and addictions. Schizophrenia was the most frequent case of psychosis. Not only the patient’s conditions are very poor, he hates himself for being unsuccessful in his job but also his family life is seriously disorganized and his relations with other people are disturbed. The question whether the patient’s marriage is in force arises quite often in such cases as well. The patient with neurosis has a feeling of mental discomfort without realizing the real reasons. Unrecognized problems have a great impact on interpersonal relations with family and other people. The aim of psychotherapy in such cases is to find the actual causes of conflicts and to teach the patient how to cope with them. All kinds of addictions are often accompanied by psychosis and neurosis. Alcoholism is the most common addiction dealt with in the Diocese Family and Pastoral Counseling Center in Katowice because it seriously disturbs family life. It often goes together with financial problems, disorganized family life, upbringing problems, losing a job, losing respect as well as co-addiction which makes it difficult to overcome the alcoholic problems. It is very hard to persuade the patient with alcoholic and psychosis problems to start the therapy. Motivating the patient and initiating the therapy is the essential element of helping both the patient and his family.